Study of Steam Turbine Unit Operation Using Natural Gas Combustion in Pure Oxygen to Ensure Decarbonisation through Gas Path Modernization (using the Example of a TGM-94 (EP-500/140) steam boiler) - Shaposhnikov V.V.; Kuban State Technological University, Krasnodar, Russian Federation; Kocharyan E.V.; Batko D.N.; Shelest N.A. (Problems of the Regional Energetics, 2024)
The research is aimed at substantiating the technical use of natural gas combustion in an environment with a high oxygen content and, in the long-run objective - in pure oxygen in a steam turbine power unit. To achieve this aim, the following problems were solved: the development of a mathematical model of a steam turbine power unit for operation when burning natural gas in pure oxygen, a numerical study of the power unit operation when replacing air with oxygen from 0 to 100%, and an assessment of the efficiency of the equipment in these modes. The most important result is an increase in the efficiency of the steam turbine power unit when switching to burning natural gas in an environment with a high oxygen content. The significance of the results obtained is to ensure the efficiency of CO2 capture from flue gases without a complete reconstruction of the facility. The object of the study was the Krasnodar Thermal Power Plant. In the study, the previously verified mathematical model of the power unit was modified. The model was created using the Boiler Designer software product. The mathematical model was modified by zeroing air leaks into the boiler gas path, replacing the regenerative air heater with a tubular one, and bypassing the air heater along the flue gases when operating on an oxygen-air mixture. The maximum increase in the boiler unit efficiency is 0.6% and is in the range of air substitution with oxygen from 40 to 60%.